A comparative study of insertion/deletion polymorphisms applied among Southwest, South and Northwest Chinese populations using Investigator® DIPplex. (March 2016) - Wang, Li; Lv, Meili; Zaumsegel, Daniel; Zhang, Lushun; Liu, Fengji; Xiang, Jihua; Li, Jun; Schneider, Peter M.; Liang, Weibo; Zhang, Lin
Highlights: 591 individuals from seven Chinese populations were tested for 30 InDel markers. Populations analysis revealed a higher FST value in Uyghur. A difference between Uyghur and the other six populations tested was detected by STRUCTURE analysis. Results are in line with previously studied global populations indicating the usefulness of this marker set for forensic identity testing. Abstract: The low mutation rates, short amplicon sizes and length variation characteristics of biallelic insertion/deletion polymorphisms (INDELs) are features that allow combining advantages of both STR and SNP markers for genetic analysis. The Qiagen Investigator DIPplex kit contains 30 biallelic autosomal INDELs plus Amelogenin for forensic personal identification and parentage testing. This study compares general performances, forensic and population data collected in 7 Chinese ethnic populations (Han, Tibetan, Yi, Zhuang, Dong, Miao and Uyghur) from three areas (Southwest, South and Northwest) of China by DIPplex kit. There were no significant departures from Hardy–Weinberg equilibrium (HWE) of the 30 markers in all the tested populations after Bonferroni correction. The combined matching probabilities ranged from 1.4273 × 10 −10 for the Dong minority to 1.2817 × 10 −12 for the Uyghur minority. The combined power of paternity exclusion was from 0.9854 to 0.9968. All pairwise genetic differences ( F ST ) between the seven ethnic groups were less than 0.05, and the results of STRUCTURE analysis did not indicate the presence of substructures suggesting genetic similarity among the populations in these three areas. The DIPplex kit can be used as a good additional tool for forensic personal identification in these three areas of China.